LINGUOCULTURAL CHARACTERISTICS OF UZBEK AND FRENCH ANTHROPONYM (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
In this article, the specific features of Uzbek and French anthroponyms are analyzed, two linguistic materials provide the national identity of Uzbek anthroponymy. These are: native Turkic names and Uzbek names. Discourse analysis of French anthroponames is formed on the basis of linguistic theory, and the methodological basis of its study is structuralism.